Taxonomic revision of the genus Chaethippus Duda, 1930 (Diptera: Chloropidae) with the description of four species - Riccardi, Paula Raile (Zootaxa, 2020)
The monotypic genus Chaethippus Duda is revised, including the description of four new species from South America and a key to all species. Detailed illustrations of morphological features are also given using light and scanning electron microscopy. The affinities of Chaethippus within Oscinellinae are briefly addressed.